Exploring the association between a parent's exposure to Adverse Childhood Experiences (ACEs) and outcomes of depression and anxiety among their children. (June 2020) - Haynes, Eboni; Crouch, Elizabeth; Probst, Janice; Radcliff, Elizabeth; Bennett, Kevin; Glover, Saundra
Highlights: Traumatic experiences are associated with parenting behaviors later in life. It is important to address the intergenerational nature and consequences of ACEs, Understanding the role of caregiver ACEs in children's mental health is important. Caregivers with depression/anxiety increase children's risk of depression/anxiety. Caregivers with four or more ACEs increase children's risk of depression/anxiety. Abstract: Traumatic experiences are associated with parenting behaviors later in life, placing offspring at an increased risk of ACE exposure. As depression and anxiety are among the most prevalent mental health disorders in the U.S., this study sought to examine the role of parental ACE exposure in their children's experiences of depression/anxiety. Using data from the 2014 to 2016 linked South Carolina Behavioral Risk Factor Surveillance System (BRFSS) and the Children's Health Assessment Survey (CHAS), we found that a caregiver who has been exposed to four or more ACEs increases the odds of their child developing depression and/or anxiety three-fold (aOR 3.01; 95% CI 1.59–5.69). Additionally, having a caregiver with depression/anxiety increases the odds of their child developing depression/anxiety two-fold compared to caregivers with no ACEs (aOR 2.24; 95% CI 1.41–3.57). These findings provide additional support for the screening of caregivers for ACE exposures and children for depression/anxiety as well as for the adoption of trauma-informed approaches to address the consequences of trauma and build resilience.